Discriminating functional and non-functional p53 in human tumours by p53 and MDM2 immunohistochemistry - Nenutil, Rudolf; Šmardová, Jana; Pavlová, Šárka; Hanzelková, Zina; Müller, Petr; Fabian, Pavel; Hrstka, Roman; Janotová, P; Radina, Martin; Lane, D. P; Coates, P. J; Vojtěšek, Bořivoj (Journal of pathology, 2005)
Mutation and/or loss of the TP53 tumour suppressor gene is the single most common genetic abnormality in human cancer. The majority of TP53 mutations lead to stabilization of the protein, so that immunohistochemical staining for p53 can suggest mutation status in many cases. However, various false-positive and false-negative situations mean that simple immunostaining for p53 is not informative in a substantial number of tumours. In the present study, a series of 119 human cancers were immunostained using a highly sensitive technique that detects the low levels of wild-type protein expressed in normal cells, such that homozygous gene deletion or non-sense TP53 mutation can be identified by an absence of staining. TP53 gene status was also assessed using FASAY as a genetic/functional screen and in selected cases by direct sequencing. A quantitative scoring system was employed to assess p53 levels, and p53 post-translational modification was evaluated using antibodies that detect specific phosphorylation sites. Phosphorylated p53 correlated with total p53 levels and did not improve the prediction of TP53 mutation status. The transcriptional activity of TP53 was determined by staining for two downstream target genes, p21(WAF1) and MDM2, and statistical correlations between MDM2/p21(WAF1) and p53 were found in tumours with wild-type, but not mutant TP53. Measurement of staining for p53 and MDM2 accurately identifies the TP53 status of tumours. This simple and cost-effective method, applicable to automated staining and quantitation methods, improves the identification of TP53 status over standard methods for p53 immunostaining and provides information about tumour p53 phenotype that is complementary to genotyping data. Copyright (c) 2005 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: antigen Ki-67; Ki-67 Antigen; nádory; geny p53; nádory prsu; nádory endometria; imunohistochemie; fosforylace; Adenocarcinoma; Uterine Cervical Neoplasms; lidé; ženské pohlaví; DNA nádorová; genetická transkripce; nádory děložního čípku; Proto-Oncogene Proteins c-mdm2; financování organizované; Endometrial Neoplasms; protoonkogenní proteiny c-mdm2; mutace; Breast Neoplasms; Carcinoma, Squamous Cell; Female; Financing, Organized; spinocelulární karcinom; Cyclin-Dependent Kinase Inhibitor p21; nádory vaječníků; adenokarcinom; Genes, p53; Mutation; Humans; Ovarian Neoplasms; nádorový supresorový protein p53; Neoplasms; Tumor Suppressor Protein p53; DNA, Neoplasm; Phosphorylation; Immunohistochemistry; Transcription, Genetic; inhibitor p21 cyklin-dependentní kinasy